The Influence of Product Knowledge and E-Banking Technology on the Interest of Muslim Communities in Using BSI Services at Luwuk Branch, Banggai Regency - Rahman Syahid. P; Nurhaliza Rahmalia Palureng (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
This study aims to analyze the influence of product knowledge and e-banking technology on the interest of Muslim communities in using the services of Bank Syariah Indonesia (BSI) at the Luwuk Branch, Banggai Regency. Islamic banking has experienced significant development in Indonesia, although public utilization remains relatively low despite the country's large Muslim population. Product understanding and technological development are considered important factors influencing customer decisions in selecting Islamic banking services. This study employed a quantitative approach using an explanatory survey design. Data were collected through structured questionnaires distributed to 50 respondents who were customers of BSI Luwuk Branch using incidental sampling techniques. Data analysis included validity and reliability testing, classical assumption tests, multiple linear regression analysis, partial hypothesis testing (t-test), and simultaneous testing (F-test) using SPSS version 25. The findings indicate that product knowledge has a positive and significant influence on customer interest with a t-value of 8.998 and a significance value of 0.000. E-banking technology also demonstrated a positive and significant influence with a t-value of 4.650 and a significance value of 0.000. Simultaneous analysis revealed that both variables significantly influence customer interest with an F-value of 99.524 and a significance value of 0.000. Product knowledge and digital banking services play important roles in increasing the adoption of Islamic banking services in regional communities.